Penetration and diffusion of hydrogen in Mg2Ni: A first-principles investigation. (2nd February 2017) - Li, Guang-Xu; Lan, Zhi-Qiang; Tseng, Yu-Sheng; Zhou, Wen-Zheng; Guo, Jin; Chan, Sammy Lap Ip
Abstract: First-principles calculations have been used to study the hydrogen adsorption and diffusion in both hexagonal Mg2 Ni surface and bulk Mg2 Ni, and the hydrogen diffusion rate in bulk Mg2 Ni is evaluated. The calculation shows that the adsorption energies on Mg2 Ni (100) surface are much higher than in bulk Mg2 Ni. For hydrogen diffusing from Mg2 Ni (100) surface to subsurface, three diffusion pathways have been studied, and the lowest energy barrier is found to be 0.64 eV. To study the hydrogen atom diffusion in bulk Mg2 Ni, nine possible diffusion paths have been considered. The results show hydrogen diffusion from NiNi bridge sites to the most nearby MgNi bridges site is energetically more favorable than the other paths. The energy barrier of this process is 0.34eV, which is close to experimental data of 0.28 ± 0.04 eV. The temperature dependence of the jump rates has been investigated in some details using harmonic transition state theory and semi-classically corrected harmonic transition state theory. The calculated diffusion constant is in good agreement with the experimental data. Highlights: H adsorption and diffusion in Mg2 Ni were studied using first-principles calculations. Adsorption energies for H on Mg2 Ni (100) surface are much higher than that in bulk. Hydrogen diffusion path from NiNi site to nearby MgNi site is most likely.